BAGAIMANA PENGELOLAAN PENGETAHUAN, TEKNOLOGI BERKELANJUTAN, DAN INOVASI YANG MEMPENGARUHI KEBERLANJUTAN BISNIS - Novalensiago, Monica; Satyani, Fatma (Fortunate Business Review, 2021)
To ensure business sustainability, it's paying attention to the structure of the economic field and the organization itself. There are many critical aspects for the sustainable business landscape, that is to say, profit is no longer the only purpose of their existence. The present article takes a dimensional view of the Business Models (BMs) process, knowledge management, sustainable technology, and innovations as sustainable business key factors. It can be argued that success in managing changes is crucial to any organization to sustain and succeed in the present highly competitive and continuously evolving business environment. Hence, the purpose of this article is to provide a critical review of some of the theories and approaches for a sustainable business nowadays. The article also concludes with recommendations for further research. Keywords: business sustainability, knowledge management, sustainable technology, innovations